Agmatine Prevents Adaptation of the Hippocampal Glutamate System in Chronic Morphine-Treated Rats - Xiao-Fei Wang; Tai-Yun Zhao; Rui-Bin Su; Ning Wu; Jin Li (Neuroscience Bulletin, 2016)

Index-based evaluation of vegetation response to meteorological drought in Northern China - Rui Li; Jing’ai Wang; Tianjie Zhao; Jiancheng Shi (Natural Hazards, 2016)

A monotonically declining elevational pattern of bacterial diversity in freshwater lake sediments - Jin Zeng; Dayong Zhao; Huabing Li; Rui Huang; Jianjun Wang; Qinglong L. Wu (Environmental Microbiology, 2016)
Summary The distribution patterns of bacterial communities along elevational gradients remain unexplored in aquatic ecosystems. This study investigated the diversity and community composition of bacteria in the sediments of lakes along a mountainside elevational gradient from 525 to 4 490 m in western China. The bacterial alpha diversity (taxonomic richness and phylogenetic diversity) at different sediment depths decreased monotonically with the increasing elevation, and the beta diversity (dissimilarity between lakes) increased significantly with the increasing elevation distance. Both elevation and chemical variables including pH and carbon/nitrogen ratio were identified as major factors affecting the bacterial diversity. Especially, bacterial alpha/beta diversity was significantly related to both chemical and elevational gradients in the surface sediments, whereas elevation overwhelmed chemical factors in influencing the bacterial alpha/beta diversity in the subsurface sediments. Phylogenetic structure analysis demonstrated that environmental filtering was the most important process affecting the bacterial community assembly along the elevational gradient, and the strength of environmental filtering increased towards high elevations. In summary, we observed for the first time a monotonically decreasing elevational pattern in bacterial diversity of freshwater lake sediments, which is mainly driven by elevation associated environmental factors.

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Augmented expression of gamma-glutamyl transferase 5 (GGT5) impairs testicular steroidogenesis by deregulating local oxidative stress - Wei Li; Zhi-qun Wu; Shun Zhang; Rui Cao; Jie Zhao; Zhi-jian Sun; Wei Zou (Cell and Tissue Research, 2016)

Increasing the recovery of heavy metal ions using two microbial fuel cells operating in parallel with no power output - Xiaohui Wang; Jing Li; Zhao Wang; Hairti Tursun; Rui Liu; Yanmei Gao; Yuan Li (Environmental Science and Pollution Research, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Exogenous Abscisic Acid Alleviates Cadmium Toxicity by Restricting Cd2+ Influx in Populus euphratica Cells - Yansha Han; Shaojie Wang; Nan Zhao; Shurong Deng; Chenjing Zhao; Nianfei Li; Jian Sun; Rui Zhao; Huilan Yi; Xin Shen; Shaoliang Chen (Journal of Plant Growth Regulation, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

A new epidioxy-tetracyclic triterpenoid from Poria cocos Wolf - Shiping Li; Zhixin Wang; Rui Gu; Yiwu Zhao; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

An analysis of physiological index of differences in drought tolerance of tomato rootstock seedlings - Xuehui Yao; Rui Yang; Fukuan Zhao; Shaohui Wang; Changbao Li; Wenchao Zhao (Journal of Plant Biology, 2016)

Cardiotoxicity screening: a review of rapid-throughput in vitro approaches - Xichun Li; Rui Zhang; Bin Zhao; Christoph Lossin; Zhengyu Cao (Archives of Toxicology, 2016)

Progression and inflammation of human myeloid leukemia induced by ambient PM2.5 exposure - Xiao-Ting Jin; Mei-Lan Chen; Rui-Jin Li; Quan An; Li Song; Yi Zhao; Hong Xiao; Long Cheng; Zhuo-Yu Li (Archives of Toxicology, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Two new compounds from the roots of Ilex pubescens and their cytotoxic activity - Huan Xiong; Fang Zhao; Jiayi Bi; Yang Zhang; Guiyun Zhao; Xue Chen; Yuncong Li; Rui Yan; Qiang Zhao; Hua Qiao; Guogang Zhang (Journal of Natural Medicines, 2016)

Extracellular ATP mediates cellular K+/Na+ homeostasis in two contrasting poplar species under NaCl stress - Nan Zhao; Shaojie Wang; Xujun Ma; Huipeng Zhu; Gang Sa; Jian Sun; Nianfei Li; Chenjing Zhao; Rui Zhao; Shaoliang Chen (Trees, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Ochrobactrum endophyticum sp. nov., isolated from roots of Glycyrrhiza uralensis - Li Li; Yan-Qiong Li; Zhao Jiang; Rui Gao; Salam Nimaichand; Yan-Qing Duan; Dilfuza Egamberdieva; Wei Chen; Wen-Jun Li (Archives of Microbiology, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

First survey of parasitic helminths of goats along the Han River in Hubei Province, China - Xin Yang; Robin B. Gasser; Rui Fang; Jinrong Zeng; Kaixiang Zhu; Mingwei Qi; Zongze Zhang; Li Tan; Weiqiang Lei; Yanqin Zhou; Junlong Zhao; Min Hu (Acta Parasitologica, 2016)
Diseases caused by parasitic helminths cause considerable production and economic losses in livestock worldwide. Understanding the epidemiology of these parasites has important implications for controlling them. The main purpose of the present study was to estimate the prevalence of key parasitic helminths in goats along the Han River in Zhanggang, Hubei Province (from January to December 2014). We used faecal flotation and sedimentation techniques as well as PCR-based DNA sequencing to detect and identify helminths. Results showed that the prevalence of helminths was high throughout the year, particularly for gastrointestinal nematodes. These first findings provide useful baseline information for goat helminths in Zhanggang, and a starting point for the implementation of control programs. With an increased expansion of the goat industry in China, the findings also emphasise the need to undertake prevalence surveys in other regions of China where extensive farming practices are used.